Erosion and sedimentation - Julien, Pierre Y. (Cambridge University Press, 2010)
"The second edition of this acclaimed, accessible textbook brings the subject of sedimentation and erosion completely up-to-date, providing an excellent primer on both fundamental concepts of sediment-transport theory and methods for practical applications. The structure of the first edition is essentially unchanged, but all the chapters have been updated, with several chapters reworked and expanded significantly. Examples of the new additions include the concept of added mass, the Modified Einstein Procedure, sediment transport by size fractions, sediment transport of sediment mixtures, and new solutions to the Einstein Integrals. Many new examples and exercises have been added. Erosion and Sedimentation is an essential textbook on the topic for students in civil and environmental engineering and the geosciences, and also as a handbook for researchers and professionals in engineering, the geosciences and the water sciences"-- Provided by publisher.
Keywords: Erosion.; Sedimentation and deposition.; elektronické knihy; electronic books